Lithium-ion electrolyte resistant hot melt adhesive and preparation method thereof

A maleic anhydride-modified rubber resin, prepared by modifying maleic anhydride with a compound of highly active polyisobutylene and polybutadiene, combined with amorphous α-olefin copolymer and hydrogenated tackifying resin, solves the problems of high metal adhesion, electrolyte swelling resistance, rapid curing and wide workability of adhesives for lithium batteries, thus meeting the production requirements of consumer electronics.

CN121914646BActive Publication Date: 2026-08-25SHANGHAI JINQIANG ADHESIVE
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202610365304.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-03-24
Publication Date
2026-08-25
Estimated Expiration
2046-03-24

AI Technical Summary

Technical Problem

Existing lithium battery adhesives cannot simultaneously achieve high metal adhesion, resistance to electrolyte swelling, rapid curing, and wide application range, thus failing to meet the high-speed production cycle required for consumer electronics.

Method used

A maleic anhydride-modified rubber resin, prepared by grafting maleic anhydride onto a compound of highly active polyisobutylene and polybutadiene, is combined with amorphous α-olefin copolymer, modified wax, and hydrogenated tackifying resin to form a hot melt adhesive with a three-dimensional network structure, providing high metal adhesion, resistance to electrolyte swelling, rapid curing, and a wide application window.

Benefits of technology

It achieves a balance between long-term structural stability in lithium battery electrolyte environments and consumer electronics-grade production speed, providing high metal adhesion, superior resistance to electrolyte swelling, rapid positioning and curing, and a wide application window.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The present application relates to the technical field of hot melt adhesive, in particular to a lithium-ion electrolyte-resistant hot melt adhesive and a preparation method thereof, the lithium-ion electrolyte-resistant hot melt adhesive comprises the following components in parts by weight: maleic anhydride modified rubber resin 15-35 parts; amorphous alpha-olefin copolymer 25-50 parts; modified wax 5-15 parts; hydrogenated tackifying resin 20-40 parts; antioxidant 0.1-2 parts; wherein the maleic anhydride modified rubber resin is prepared by grafting modification of high-activity polyisobutylene and polybutadiene after compounding. Through comprehensive optimization of formula combination, the product provided can form strong chemical anchoring with metal base material, can maintain structural stability in lithium battery electrolyte environment for a long time, and can meet the high-speed production rhythm of consumer electronics level.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of hot melt adhesive technology, specifically to a lithium-ion electrolyte resistant hot melt adhesive and its preparation method. Background Technology

[0002] With the rapid development of the consumer electronics and new energy vehicle industries, higher demands are being placed on the energy density, safety, and production efficiency of lithium-ion batteries. In the packaging, tab fixing, termination tape bonding, and internal structural reinforcement of lithium battery cells, the performance of adhesive materials directly determines the long-term stability and safety of the battery. The internal environment of lithium batteries is extremely harsh, mainly due to: prolonged contact with carbonate electrolytes, where ordinary adhesives are prone to swelling, debonding, or even dissolving; the low surface energy of substrates such as aluminum tabs, copper foil, and the inner layer of aluminum-plastic film (nylon / polypropylene) results in poor wettability of polar adhesives; the fast production cycle of consumer electronics-grade batteries requires hot melt adhesives to cure and reach operational strength within seconds; and the need to withstand thermal shocks ranging from -40℃ to 85℃ or even higher.

[0003] Currently, adhesive materials used in lithium batteries are mainly divided into three categories: First, acrylic pressure-sensitive adhesives, which have decent electrolyte resistance but low initial tack, poor high-temperature tack retention, and are mostly solvent-based, making them environmentally unfriendly; Second, rubber-based hot melt adhesives, which have fast application speed and strong adhesion to non-polar substrates. For example, Chinese patent application (publication number CN114015383A) discloses a hot melt adhesive with excellent electrolyte resistance and its preparation method. By using a combination of specific polyolefin elastomers and rubber materials in the hot melt adhesive, its electrolyte resistance is improved, but its adhesion to polar substrates such as metals is insufficient; Third, polyurethane or epoxy resin structural adhesives. For example, Chinese patent (authorization announcement number CN115895496B) discloses an electrolyte-resistant hot melt adhesive tape and its preparation method and application. It mainly solves the problem of poor adhesion to PET substrates by using maleic anhydride-modified polyolefins and other compositions, but the curing time is as long as several minutes to several hours, which cannot match the high-speed production cycle of consumer electronics. Summary of the Invention

[0004] To address the aforementioned issues, this invention provides a lithium-ion electrolyte-resistant hot melt adhesive. Through comprehensive optimization of the formulation, the product can form a strong chemical anchor with the metal substrate and maintain structural stability in the lithium battery electrolyte environment for a long period of time, while also meeting the high-speed production cycle requirements of consumer electronics.

[0005] This invention provides a lithium-ion electrolyte-resistant hot melt adhesive, which, by weight, comprises the following components: 15-35 parts of maleic anhydride modified rubber resin; Amorphous α-olefin copolymer (APAO) 25-50 parts; 5-15 parts of modified wax; 20-40 parts of hydrogenated tackifying resin; Antioxidant 0.1-2 parts; The maleic anhydride-modified rubber resin is prepared by grafting maleic anhydride onto a compound of highly active polyisobutylene and polybutadiene.

[0006] In one embodiment, the lithium-ion electrolyte-resistant hot melt adhesive comprises, by weight, the following raw materials: 20-30 parts of maleic anhydride modified rubber resin; 30-40 parts of amorphous α-olefin copolymer; 8-10 parts of modified wax; 30-35 parts of hydrogenated tackifying resin; Antioxidant 0.5-1 part.

[0007] Existing lithium battery adhesives cannot simultaneously achieve high metal adhesion, resistance to electrolyte swelling, rapid curing, and wide application range, thus failing to meet practical application requirements. Previous attempts to improve polarity by introducing commercially available maleic anhydride-grafted resin into hot melt adhesive systems resulted in insufficient initial bond strength and electrolyte aging strength, failing to meet practical application needs. During the research process, this invention discovered that a maleic anhydride-modified rubber resin, prepared by grafting maleic anhydride onto a highly reactive polyisobutylene and polybutadiene compound, combined with APAO, modified wax, and hydrogenated tackifying resin, provides a product that combines high metal adhesion, superior resistance to electrolyte swelling, rapid positioning and curing, and a wide application window. The possible reasons are as follows: By compounding highly reactive polyisobutylene with high-vinyl polybutadiene and then grafting it with maleic anhydride, a maleic anhydride-modified rubber resin with a three-dimensional network structure that combines rigidity and flexibility is obtained. This effectively inhibits the free diffusion of polymer chains in the solvent while providing high-density anchoring sites at the interface between the adhesive and the metal. Combined with APAO's rapid physical curing, modified wax interface reinforcement, and hydrogenated resin's hydrolysis resistance, a balance is achieved between high adhesion, swelling resistance, rapid curing, and a wide application window.

[0008] In one embodiment, the acid value of the maleic anhydride modified rubber resin is 150-240 mgKOH / g.

[0009] In one embodiment, the acid value of the maleic anhydride modified rubber resin is 166-229 mgKOH / g.

[0010] In one embodiment, the number-average molecular weight Mn of the highly active polyisobutylene is 600-2000.

[0011] In one embodiment, the number-average molecular weight Mn of the highly active polyisobutylene is 750-1300.

[0012] In one embodiment, the 1,2-vinyl content of the polybutadiene is 18-35%.

[0013] In one embodiment, the 1,2-vinyl content of the polybutadiene is 20-30%.

[0014] In one embodiment, the weight ratio of the highly active polyisobutylene to polybutadiene is 85-98:2-15.

[0015] In one embodiment, the weight ratio of the highly active polyisobutylene to polybutadiene is 90-95:5-10.

[0016] In one embodiment, the grafting amount of maleic anhydride is 15-35% of the total weight of highly active polyisobutylene and polybutadiene.

[0017] In one embodiment, the grafting amount of maleic anhydride is 18-28% of the total weight of highly active polyisobutylene and polybutadiene.

[0018] In one embodiment, the method for preparing the maleic anhydride-modified rubber resin includes the following steps: Highly reactive polyisobutylene and polybutadiene are mixed and dehydrated under vacuum heating until the moisture content is <500ppm. Maleic anhydride is added under nitrogen protection, and the mixture is heated to 180-220℃ with stirring. During the reaction, the characteristic peak of carbon-carbon double bonds is monitored by infrared spectroscopy. The reaction is stopped after the carbon-carbon double bonds have completely disappeared. Vacuum is then applied to -0.095MPa-0.1MPa to remove unreacted maleic anhydride until the acid value of the material reaches 150-240 mgKOH / g. The material is then discharged and cooled to obtain maleic anhydride modified rubber resin.

[0019] Furthermore, this invention obtains a maleic anhydride-modified rubber resin with an acid value of 150-240 mgKOH / g by reacting highly reactive polyisobutylene with a number-average molecular weight (Mn) of 600-2000 with polybutadiene until the carbon-carbon double bonds are completely eliminated by infrared monitoring. This provides a moderate crosslinking network and sufficient anhydride functional groups, ensuring that the polybutadiene segments fully participate in the grafting and coupling reactions, achieving the best balance between strength, viscosity and swelling resistance.

[0020] In one embodiment, the amorphous α-olefin copolymer is an amorphous polypropylene copolymer or a propylene-butene copolymer.

[0021] In one embodiment, the viscosity of the amorphous α-olefin copolymer at 190°C is 5000-10000 mPa·s.

[0022] In one embodiment, the amorphous α-olefin copolymer is selected from the Evonik VESTOPLAST® series.

[0023] In one embodiment, the amorphous α-olefin copolymer is at least one of VESTOPLAST® 308 or VESTOPLAST® 608.

[0024] In one embodiment, the modified wax is maleic anhydride-grafted polypropylene wax or maleic anhydride-modified polyethylene wax.

[0025] In one embodiment, the modified wax is at least one of Honeywell AC® 597A or Honeywell AC® 907.

[0026] In one embodiment, the hydrogenated tackifying resin is a hydrogenated C5 petroleum resin or a hydrogenated C9 petroleum resin.

[0027] In one embodiment, the softening point of the hydrogenated tackifying resin is 100-150°C.

[0028] In one embodiment, the hydrogenated tackifying resin is at least one of Eastman Regaltac™ H-142R or Henghe New Materials HP-140.

[0029] Based on the amorphous α-olefin copolymer in the system, by introducing maleic anhydride-grafted polypropylene wax or maleic anhydride-modified polyethylene wax and hydrogenated tackifying resin with a softening point of 100-150℃, the workability is guaranteed while providing additional anhydride / carboxyl anchoring points to further improve the bonding strength and resistance to electrolyte hydrolysis.

[0030] In one embodiment, the lithium-ion electrolyte resistant hot melt adhesive further includes 0.1-3 parts of pigment by weight.

[0031] In one embodiment, the lithium-ion electrolyte resistant hot melt adhesive further includes 1-2 parts of pigment by weight.

[0032] In one embodiment, the pigment is at least one of cobalt blue, cobalt green, or titanium chromium brown.

[0033] In one embodiment, the pigment is designated BASF Sicopal® blue K6310.

[0034] In one embodiment, the antioxidant includes hindered phenolic antioxidants.

[0035] In one embodiment, the hindered phenolic antioxidant includes BASF antioxidant 1010.

[0036] Another aspect of the present invention provides a method for preparing a lithium-ion electrolyte resistant hot melt adhesive, comprising the following steps: Maleic anhydride-modified rubber resin, amorphous α-olefin copolymer, modified wax, hydrogenated tackifying resin, pigment and antioxidant are added to a reaction vessel, heated to 160-200℃ under vacuum conditions, stirred until completely melted and uniformly mixed, and then discharged, cooled and granulated to obtain lithium-ion electrolyte resistant hot melt adhesive or molding.

[0037] The third aspect of this invention provides an application of a lithium-ion electrolyte resistant hot melt adhesive for bonding, reinforcement, or protection in lithium-ion battery chemical systems.

[0038] The lithium-ion electrolyte resistant hot melt adhesive provided by this invention can be effectively applied to battery tab bonding and fixing, cell termination tape coating, aluminum-plastic film inner layer bonding, internal structural component reinforcement or short-circuit insulation protection. It can be applied using conventional hot melt coating machines, dispensing machines or roller coating machines without additional equipment modification, and has extremely high industrial promotion value.

[0039] Beneficial effects 1. This invention provides a lithium-ion electrolyte resistant hot melt adhesive. Through comprehensive optimization of the formula combination, the provided product can not only form a strong chemical anchor with the metal substrate, but also maintain structural stability in the lithium battery electrolyte environment for a long time, while meeting the high-speed production cycle of consumer electronics.

[0040] 2. During the research process, this invention discovered that by using highly active polyisobutylene and polybutadiene compounded and then modified by maleic anhydride grafting, the resulting maleic anhydride modified rubber resin, combined with APAO, modified wax, hydrogenated tackifying resin and other components, provides a product that combines high metal adhesion, super strong resistance to electrolyte swelling, rapid positioning and curing, and a wide application window.

[0041] 3. This invention uses highly active polyisobutylene with a number-average molecular weight (Mn) of 600-2000 to react with polybutadiene until the carbon-carbon double bonds are completely eliminated by infrared monitoring, and then stops the reaction to obtain a maleic anhydride modified rubber resin with an acid value of 150-240 mgKOH / g. This provides a moderate crosslinking network and sufficient anhydride functional groups to ensure that the polybutadiene segments fully participate in the grafting and coupling reactions, achieving the best balance between strength, viscosity and swelling resistance.

[0042] 4. Based on the amorphous α-olefin copolymer in the system, by introducing maleic anhydride-grafted polypropylene wax or maleic anhydride-modified polyethylene wax and hydrogenated tackifying resin with a softening point of 100-150℃, the workability is guaranteed while providing additional anhydride / carboxyl anchoring points to further improve the bonding strength and resistance to electrolyte hydrolysis.

[0043] 5. The lithium-ion electrolyte resistant hot melt adhesive provided by this invention can be effectively applied to battery tab bonding and fixing, cell termination tape coating, aluminum-plastic film inner layer bonding, internal structural component reinforcement or short-circuit insulation protection. It can be applied using conventional hot melt coating machines, dispensing machines or roller coating machines without additional equipment modification, and has extremely high industrial promotion value. Detailed Implementation

[0044] The raw material information in each embodiment and comparative example is as follows: Highly reactive polyisobutylene: grades HRPB550 (Mn=550), HRPB750 (Mn=750), HRPB1000 (Mn=1000), HRPB1300 (Mn=1300), and HRPB2300 (Mn=2300), all sourced from Daelim, South Korea. Polybutadiene: grades Ricon131 (20% 1,2-vinyl content) and Ricon134 (30% 1,2-vinyl content), both sourced from Krevili.

[0045] Maleic anhydride: CAS number 108-31-6. Amorphous α-olefin copolymers: Evonik VESTOPLAST® 308 (viscosity 8000 mPa·s @ 190℃) and VESTOPLAST® 608 (viscosity 9000 mPa·s @ 190℃).

[0046] Modified waxes: Honeywell AC®597A (maleic anhydride-grafted polypropylene wax), Honeywell AC®907 (maleic anhydride-grafted polypropylene wax); Clariant Licocene® PP 6502 (polypropylene wax).

[0047] Hydrogenated tackifying resins: Eastman Regaltac™ H-142R (hydrogenated C5 petroleum resin, softening point 142℃); Henghe New Materials HP-140 (hydrogenated C9 petroleum resin, softening point 140℃); Henghe New Materials HHQ-140 (non-hydrogenated C9 petroleum resin).

[0048] Commercially available comparison resins: Lubrizol ADDCONATE® H (maleic anhydride polyisobutylene); Clayville Ricon 130MA8 (maleic anhydride polybutadiene); Clariant PPA 330 (liquid polyolefin). Pigment: BASF Sicopal® blue K6310 (cobalt blue).

[0049] Antioxidant: BASF Irganox® 1010.

[0050] Preparation Example 1 Example 1 of the present invention provides a maleic anhydride modified rubber resin 1. The preparation method of the maleic anhydride modified rubber resin 1 includes the following steps: 95 parts of Korean Daelim high-activity polyisobutylene HRPB750 and 5 parts of Kreveli polybutadiene Ricon131 are added to a reaction vessel, and the mixture is dehydrated by vacuum heating at 100°C until the moisture content is <500ppm. Under nitrogen protection, 27.59 parts of maleic anhydride are added, and the mixture is heated to 200°C under nitrogen atmosphere and stirred until no carbon-carbon double bond characteristic peaks are detected by infrared spectroscopy. The vacuum is then turned on to -100kPa, and the unreacted maleic anhydride is removed until the acid value of the material is 229mgKOH / g. The mixture is then cooled.

[0051] Preparation Example 2 Preparation Example 2 of the present invention provides a maleic anhydride modified rubber resin 2. The preparation method of the maleic anhydride modified rubber resin 2 includes the following steps: 95 parts of Daelim reactive polyisobutylene HRPB1000 (Korea) and 5 parts of Clayville polybutadiene Ricon 134 are added to a reaction vessel. The mixture is then vacuum heated to 100°C to dehydrate until the moisture content is <500ppm. Under nitrogen protection, 22.58 parts of maleic anhydride are added. The mixture is heated to 200°C under a nitrogen atmosphere and stirred until no carbon-carbon double bond characteristic peaks are detected by infrared spectroscopy. The vacuum is then turned on to -100kPa, and the unreacted maleic anhydride is removed until the acid value of the material is 194mgKOH / g. The mixture is then cooled.

[0052] Preparation Example 3 Preparation Example 3 of the present invention provides a maleic anhydride modified rubber resin 3. The preparation method of the maleic anhydride modified rubber resin 3 includes the following steps: 95 parts of Korean Daelim high-activity polyisobutylene HRPB1300 and 5 parts of Krevelli polybutadiene Ricon134 are added to a reaction vessel, and the mixture is dehydrated by vacuum heating at 100°C until the moisture content is <500ppm. Under nitrogen protection, 18.79 parts of maleic anhydride are added, and the mixture is heated to 200°C under nitrogen atmosphere and stirred until no carbon-carbon double bond characteristic peaks are detected by infrared spectroscopy. The vacuum is then turned on to -100kPa, and the unreacted maleic anhydride is removed until the acid value of the material is 166mgKOH / g. The mixture is then cooled.

[0053] Preparation Example 4 Example 4 of the present invention provides a maleic anhydride modified rubber resin 4. The preparation method of the maleic anhydride modified rubber resin 4 includes the following steps: 90 parts of Korean Daelim high-activity polyisobutylene HRPB1300 and 10 parts of Krevelli polybutadiene Ricon131 are added to a reaction vessel, and the mixture is dehydrated by vacuum heating at 100°C until the moisture content is <500ppm. Under nitrogen protection, 23.41 parts of maleic anhydride are added, and the mixture is heated to 200°C and stirred under nitrogen atmosphere until no carbon-carbon double bond characteristic peaks are detected by infrared spectroscopy. The vacuum is then turned on to -100kPa, and the unreacted maleic anhydride is removed until the acid value of the material is 200mgKOH / g. The mixture is then cooled.

[0054] Preparation Example 5 Preparation Example 5 of the present invention provides a maleic anhydride modified rubber resin 5. The preparation method of the maleic anhydride modified rubber resin 5 includes the following steps: 95 parts of Korean Daelim high-activity polyisobutylene HRPB550 and 5 parts of Krevelli polybutadiene Ricon131 are added to a reaction vessel, and the mixture is dehydrated by vacuum heating at 100°C until the moisture content is <500ppm. Under nitrogen protection, 32.31 parts of maleic anhydride are added, and the mixture is heated to 200°C under nitrogen atmosphere and stirred until no carbon-carbon double bond characteristic peaks are detected by infrared spectroscopy. The vacuum is then turned on to -100kPa, and the unreacted maleic anhydride is removed until the acid value of the material is 279.36mgKOH / g. The mixture is then cooled.

[0055] Preparation Example 6 Preparation Example 6 of the present invention provides a maleic anhydride modified rubber resin 6. The preparation method of the maleic anhydride modified rubber resin 6 includes the following steps: 95 parts of Korean Daelim high-activity polyisobutylene HRPB2300 and 5 parts of Krevelli polybutadiene Ricon131 are added to a reaction vessel, and the mixture is dehydrated by vacuum heating at 100°C until the moisture content is <500ppm. Under nitrogen protection, 12.68 parts of maleic anhydride are added, and the mixture is heated to 200°C under nitrogen atmosphere and stirred until no carbon-carbon double bond characteristic peaks are detected by infrared spectroscopy. The vacuum is then turned on to -100kPa, and the unreacted maleic anhydride is removed until the acid value of the material is 119.74mgKOH / g. The mixture is then cooled.

[0056] Preparation Example 7 Preparation Example 7 of the present invention provides a maleic anhydride modified rubber resin 7. The preparation method of the maleic anhydride modified rubber resin 7 includes the following steps: adding 95 parts of Korean Daelim high-activity polyisobutylene HRPB1300 and 5 parts of Clayville polybutadiene Ricon134 to a reaction vessel, dehydrating by vacuum heating at 100°C until the moisture content is <500ppm, adding 13.34 parts of maleic anhydride under nitrogen protection, heating to 200°C under nitrogen atmosphere and stirring until the acid value of the material is 133mgKOH / g, and then cooling.

[0057] Examples 1-8, Comparative Examples 1-8 Examples 1-8 and Comparative Examples 1-8 of the present invention provide a lithium-ion electrolyte resistant hot melt adhesive, the formulation of which is shown in Table 1 by weight.

[0058] Table 1

[0059] In Table 1, “(20)” is used as an example, which means that the amount of the corresponding raw material is 20 parts by weight.

[0060] Examples 1-8 and Comparative Examples 1-8 of the present invention, on the other hand, provide a method for preparing a lithium-ion electrolyte-resistant hot melt adhesive, comprising the following steps: Maleic anhydride-modified rubber resin, amorphous α-olefin copolymer, modified wax, hydrogenated tackifying resin, pigment and antioxidant are added to a reaction vessel, heated to 180°C under vacuum, stirred until completely melted and mixed evenly, and then discharged, cooled and granulated to obtain a lithium-ion electrolyte resistant hot melt adhesive.

[0061] Performance testing 1. Viscosity: The viscosity of the hot melt adhesives provided in each example and comparative example was tested at 180°C and after being placed at 180°C for 48 hours, using GB / T 2794—2013 Determination of viscosity of adhesives—Single cylinder rotational viscometer method. The test results are shown in Tables 2 and 3.

[0062] 2. Tensile shear strength: The hot melt adhesives provided in each embodiment and comparative example were used to prepare tensile shear strength test pieces with different substrates according to the requirements of GB / T7124-2008, and tensile shear strength tests were conducted. The results are shown in Tables 2 and 3.

[0063] 3. The hot melt adhesives provided in each embodiment and comparative example were used to prepare tensile shear strength test pieces with different substrates according to the requirements of GB / T7124-2008. After immersing in lithium-ion electrolyte (m(lithium hexafluorophosphate):m(ethylene carbonate):m(propylene carbonate):m(diethyl carbonate):m(ethyl propionate)) = 15.19:30:10:30:30 at 85°C for 24 hours, tensile shear strength tests were performed. The results are shown in Tables 2 and 3.

[0064] 4. Tensile strength: The hot melt adhesives provided in each embodiment and comparative example were used to prepare 2mm thick type I tensile sheets according to the requirements of GB / T 528-2009, and tensile strength tests were conducted. The test results are shown in Tables 2 and 3.

[0065] 5. The hot melt adhesives provided in each embodiment and comparative example were used to prepare 2mm thick type I tensile sheets according to the requirements of GB / T 528-2009. After being immersed in lithium-ion electrolyte at 85℃ for 24 hours, tensile strength tests were performed. The test results are shown in Tables 2 and 3.

[0066] 6. Swelling rate after immersion in lithium-ion electrolyte: Hot melt adhesive was pressed into 20mm×20mm×1mm test pieces, and the initial mass W0 was measured. The pieces were immersed in lithium-ion electrolyte at 85℃ for 24 hours. After immersion, the surface was quickly dried with filter paper, and the mass W1 after swelling was measured. Swelling rate = (W1-W0) / W0×100%. Test results are shown in Tables 2 and 3.

[0067] Table 2

[0068] Table 3

[0069] Analysis of Tables 2 and 3 shows that the products provided in Examples 1-8 have superior overall performance compared to Comparative Examples 1-8.

Claims

1. A lithium-ion electrolyte resistant hot melt adhesive, characterized in that, The lithium-ion electrolyte resistant hot melt adhesive comprises the following components in parts by weight: 15-35 parts of maleic anhydride modified rubber resin; 25-50 parts of amorphous α-olefin copolymer; 5-15 parts of modified wax; 20-40 parts of hydrogenated tackifying resin; Antioxidant 0.1-2 parts; The maleic anhydride-modified rubber resin is prepared by grafting maleic anhydride onto a compound of highly reactive polyisobutylene and polybutadiene. The weight ratio of the highly reactive polyisobutylene to polybutadiene is 90-95:5-10, and the grafting amount of maleic anhydride is 18-28% of the total weight of the highly reactive polyisobutylene and polybutadiene. The number average molecular weight (Mn) of the highly reactive polyisobutylene is 600-2000. The acid value of the maleic anhydride-modified rubber resin is 150-240 mgKOH / g. The hydrogenated tackifying resin is hydrogenated C5 petroleum resin or hydrogenated C9 petroleum resin, and the softening point of the hydrogenated tackifying resin is 100-150℃. The modified wax is maleic anhydride-grafted polypropylene wax or maleic anhydride-modified polyethylene wax.

2. The lithium-ion electrolyte resistant hot melt adhesive according to claim 1, characterized in that, The 1,2-vinyl content of the polybutadiene is 18-35%.

3. The lithium-ion electrolyte resistant hot melt adhesive according to claim 1, characterized in that, The lithium-ion electrolyte resistant hot melt adhesive also includes 0.1-3 parts of pigment by weight.

4. A method for preparing a lithium-ion electrolyte-resistant hot melt adhesive according to claim 3, characterized in that, Includes the following steps: Maleic anhydride-modified rubber resin, amorphous α-olefin copolymer, modified wax, hydrogenated tackifying resin, pigment and antioxidant are added to a reaction vessel, heated to 160-200℃ under vacuum conditions, stirred until completely melted and uniformly mixed, and then discharged, cooled and granulated to obtain a lithium-ion electrolyte resistant hot melt adhesive.

5. The application of a lithium-ion electrolyte-resistant hot melt adhesive according to any one of claims 1-3, characterized in that, Used for bonding, reinforcement, or protection in lithium-ion battery chemistry systems.

Citation Information

Patent Citations

  • Hot melt adhesive with excellent electrolyte resistance and preparation method thereof

    CN114015383A

  • A heat-resistant electrolyte hot melt tape and its preparation method and application

    CN115895496B

  • Hot melt adhesive, preparation method thereof, secondary battery, battery module, battery pack and electric device

    CN115838575A

  • Aqueous binder, preparation method, lithium battery negative electrode and lithium battery

    CN118240510A